2017
DOI: 10.3390/en10070908
|View full text |Cite
|
Sign up to set email alerts
|

A New Miniature Wind Turbine for Wind Tunnel Experiments. Part I: Design and Performance

Abstract: Miniature wind turbines, employed in wind tunnel experiments to study the interaction of turbines with turbulent boundary layers, usually suffer from poor performance with respect to their large-scale counterparts in the field. Moreover, although wakes of wind turbines have been extensively examined in wind tunnel studies, the proper characterization of the performance of wind turbines has received relatively less attention. In this regard, the present study concerns the design and the performance analysis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
55
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 75 publications
(63 citation statements)
references
References 53 publications
8
55
0
Order By: Relevance
“…The model wind turbine employed in this wind tunnel study was developed in the previous studies of the authors. 29,30 It is a three-bladed horizontal-axis miniature wind turbine with a rotor diameter D of 15 cm and a hub height z h of 12.5 cm. Given its small size, this turbine is especially suitable for wind tunnel simulations of large wind farms.…”
Section: Model Wind Turbinementioning
confidence: 99%
See 1 more Smart Citation
“…The model wind turbine employed in this wind tunnel study was developed in the previous studies of the authors. 29,30 It is a three-bladed horizontal-axis miniature wind turbine with a rotor diameter D of 15 cm and a hub height z h of 12.5 cm. Given its small size, this turbine is especially suitable for wind tunnel simulations of large wind farms.…”
Section: Model Wind Turbinementioning
confidence: 99%
“…A servo-electric controller (henceforth referred to as the RPM controller) is connected to each DC generator to simultaneously monitor and control the value of the rotational velocity X as well as the electrical current i generated by the DC machine. We then use torque calibration of the DC machine performed in the study by Bastankhah and Port e-Agel 29 to estimate the shaft torque T and consequently the mechanical power (i.e., P mech ¼ TÁX) based on the values of i and X. The bottom of each turbine tower is also attached to a DC motor.…”
Section: For Detailed Information On the Turbine Modelmentioning
confidence: 99%
“…The main characteristic quantities of the incoming boundary-layer flow measured in the wind tunnel are summarised in Table 1. The geometric parameters of the miniature wind turbine, WiRE-01 [38], used in the wind-tunnel experiments [19] are shown in Figure 2b. The number of the computational cells in the streamwise (x), spanwise (y) and vertical (z) directions for four cases with different mesh resolution are summarised in Table 2.…”
Section: Numerical Setupmentioning
confidence: 99%
“…The sum of P e and P j is known as the converted power P conv and is computed by the product of the electrical current output I and the torque constant of the generator K [19]. Bastankhah and Porté-Agel [38] later found that, at the optimal tip speed ratio specified in this study (λ = 3.8), the ratio between P conv and P Mech equals 0.92 for this specific miniature wind turbine model, WiRE-01. The mechanical power extracted by the rotor using both the yawed ADMR parameterisation and the standard ADM without rotation is compared with the mechanical power obtained from the wind-tunnel experiments [19] in Figure 11b.…”
Section: Mechanical Power Predictionsmentioning
confidence: 99%
“…In the early stage of wake effect research, wind tunnel experiments and field measurements were used as the main experimental methods. An early wind tunnel experimental study was carried out at the National Aeronautical Research Institute (Swedish: Flygtekniska Försöksanstalten Abbreviated; FFA) and there were several more wind tunnel tests in recent years [2]. Some important onshore field measurements can be found in Tjaereborg [3], Nibe [4] and Sexbierum [5].…”
Section: Introductionmentioning
confidence: 99%